BATCH PROCESS INTEGRATION OF APPLYING TECHNOLOGY OF ACID CARMINIC PINCH - Erazo E., Raymundo (2005)
This work was developed in order to implement the PINCH technology integration batch process for carminic acid. The method used consisted of the application of the concepts of bottle necks total process (OPB) together with part-time models (TAM) and time fractionated! (TSM). The drying operation is identified as the rate limiting step of the process identifying it as an OPB plant capacity. The extraction yield was 95% w / p carminic acid with an energy savings of approximately 60% of the conventional requirement.